How Widespread Are the “Young” Neurons of the Mammalian Brain? - Ghibaudi, Marco; Bonfanti, Luca (Frontiers in Neuroscience, 2022)
After the discovery of adult neurogenesis (stem cell-driven production of new neuronal elements), it is conceivable to find young, undifferentiated neurons mixed with mature neurons in the neural networks of the adult mammalian brain. This “canonical” neurogenesis is restricted to small stem cell niches persisting from embryonic germinal layers, yet, the genesis of new neurons has also been reported in various parenchymal brain regions. Whichever the process involved, several populations of “young” neurons can be found at different locations of the brain. Across the years, further complexity emerged: i) molecules of immaturity can also be expressed by non-dividing cells born during embryogenesis, then maintaining immature features later on; ii) remarkable interspecies differences exist concerning the types, location, amount of undifferentiated neurons; iii) re-expression of immaturity can occur in aging (dematuration). These twists are introducing a somewhat different definition of neurogenesis than normally assumed, in which our knowledge of the “young” neurons is less sharp. In this emerging complexity, there is a need for complete mapping of the different “types” of young neurons, considering their role in postnatal development, plasticity, functioning, and interspecies differences. Several important aspects are at stake: the possible role(s) that the young neurons may play in maintaining brain efficiency and in prevention/repair of neurological disorders; nonetheless, the correct translation of results obtained from laboratory rodents. Hence, the open question is: how many types of undifferentiated neurons do exist in the brain, and how widespread are they?